Pengaruh Servant Leadership Dan Lingkungan Kerja Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening Pada Pt. Star Rubber Jujuhan - Putri, Bunga Henida; Candana, Dori Mittra; Mary, Hilda (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the influence of Servant Leadership and Work Environment on Employee Performance through Job Satisfaction as an intervening variable at PT. Star Rubber Jujuhan. The phenomenon shows that employee performance has not fully achieved the company's targets due to the implementation of suboptimal leadership and less supportive work environment conditions, thus impacting employee job satisfaction. The population of this study was all 75 employees of PT. Star Rubber Jujuhan with a saturated sampling technique. Data were collected through a survey using a questionnaire with a quantitative approach and analyzed using Structural Equation Modeling (SEM) with Partial Least Square (PLS) version 3.0. The results showed that Servant Leadership and Work Environment had a positive and significant effect on Employee Job Satisfaction and Performance. Job Satisfaction also had a positive and significant effect on Employee Performance and was able to mediate the influence of Servant Leadership and Work Environment on Employee Performance at PT. Star Rubber Jujuhan.